Analysis on the impact of delta T to the performance of chiller - Yeo, Zhi Hao (2022)
Chiller systems had become commonly used for large residential or commercial buildings. However, the energy consumption of the chiller system also occupied a large portion of the total energy consumption of the building. Therefore, it is very important to ensure the chiller system is able to work in the most energy efficient condition to reduce the electricity bill of the building. The reduction in the electricity bill is not only able to reduce the operating cost of the building, it also would be able to decrease the impact of the chiller system to the environment. Therefore, in order to achieve this objective, many research has been done to find out the energy saving measures to increase the energy efficiency of the chiller system. According to the research, increase temperature difference of chilled water is able to increase the energy efficiency of chiller system. However, many of the studies only concentrate on electricity saving. The trade-ofFthat came together with these savings did not take into account. Thus, this research aims to develop a model to evaluate the energy saving capability of increase AT of chilled water to the chiller system and the impact of AT of chilled water to the performance of the system. The research methodology includes: (1) Modeling of energy consumption of the chiller system (2) Validate model with case study (3) Manipulate the AT of chilled water and (4) Results analysis. At the end of this research, the increase of AT of chilled water is found to be able to reduce the energy consumption of the chilled water pump, which would increase the energy efficiency of the chiller system. For example, by increasing the AT of chilled water from 5°C to 8°C, the user would be able to save 6.41% of total energy consumption of the chiller system. In other word, the user could be able to reduce up to 6.33% of their electricity utility bill and greenhouse gases released per year. However, the increase of AT of chilled water would also increase the size required for cooling coil of AHU. Therefore, when implementing these improvement measures, the user would have to check whether the performance of AHU that connected to the chiller system is still able to be maintained at an acceptable level.